Reflecting on the Common European Framework of Reference for Languages: Learning, Teaching, and Assessment (CEFR) in the Indonesian Context - Adriadi Novawan; Susan Mila P. Alvares Tosalem; Suyik Binarkaheni; Evi Risa Mariana (Journal of English in Academic and Professional Communication, 2023)
CEFR is, in the Indonesian view, commonly associated merely with the standardized English test and rarely connected to the educational curriculum, pedagogy, and learning. This paper, therefore, aims to give an overview of the CEFR conceptualization; the 2001, 2018, and 2020 versions. The three versions or editions are concisely overviewed and then reflected to the Indonesian context. The adoption of CEFR provides opportunity for coherent relationship between policy, teaching, learning, and assessment.